Perovskite synthesis, properties and their related biochemical and industrial application - Eman Abdul Rahman Assirey (Elsevier, 2019)
The perovskite structure is shown to be the single most versatile ceramic host. Inorganic perovskite type oxides are attractive compounds for varied applications due to its large number of compounds, they exhibit both physical and biochemical characteristics and their Nano-formulation have been utilized as catalysts in many reaction due to their sensitivity, unique long-term stability and anti-interference ability. Some perovskites materials are very hopeful applicants for the improvement of effective anodic catalysts performance. Depending Perovskite-phase metal oxides distinct variety of properties they became useful for various applications they are newly used in electrochemical sensing of alcohols, glucose, hydrogen peroxide, gases, and neurotransmitters. Perovskite organometallic halide showed efficient essential properties for photovoltaic solar cells. This review presents a full coverage of the structure, progress of perovskites and their related applications. Stress is focused particularly to different methods of perovskites properties and there related application. Keywords: Alcohols sensor, Catalysts, Ceramic, Glucose, Neurotransmitters, Organometallic halide, Sensor, Solar cells